Survival of the Persian leopard (Panthera pardus saxicolor) in Iran: Primary threats and human-leopard conflicts. - Sanei, Arezoo (2011)
The frequencies of primary threats in previously identified Persian leopard (Panthera pardus saxicolor Pocock 1927) distribution range in Iran were estimated in this study conducted from 2002 to 2006 using interviews with local settlements and shepherds, hunters and rangers of the Iran Department of Environment (DoE). Habitat assessments were done to investigate prey availability, presence of human disturbance factors and presence of livestock as well as habitat suitability. Secondary data on human/livestock-leopard conflicts were obtained from records covering two years (2002-2003). The study showed that habitat disturbances followed by illegal hunting and excess of livestock are the main potential threats to the populations of Persian leopard in Iran. Most of the complaints made by local settlements in 2002-2003 were primarily wolf (Canis lupus) infestation while Persian leopard was in the mere third and second level of complaints in 2002-2003, respectively. This study recommends that local awareness programs must be conducted particularly in the conflict regions reported in this study. These information-education programs could contribute to the decrease in leopard hunting and prey poaching hence, would substantially help the local settlements in successful management of their livestock industry.